Alcohol Feeding in Mice Promotes Colonic Hyperpermeability and Changes in Colonic Organoid Stem Cell Fate. (7th November 2017) - Forsyth, Christopher B.; Shaikh, Maliha; Bishehsari, Faraz; Swanson, Garth; Voigt, Robin M.; Dodiya, Hemraj; Wilkinson, Peter; Samelco, Beata; Song, Shiwen; Keshavarzian, Ali
Abstract : Background: Alcohol increases intestinal permeability to proinflammatory microbial products that promote liver disease, even after a period of sobriety. We sought to test the hypothesis that alcohol affects intestinal stem cells using an in vivo model and ex vivo organoids generated from jejunum and colon from mice fed chronic alcohol. Methods: Mice were fed a control or an alcohol diet. Intestinal permeability, liver steatosis–inflammation, and stool short‐chain fatty acids (SCFAs) were measured. Jejunum and colonic organoids and tissue were stained for stem cell, cell lineage, and apical junction markers with assessment of mRNA by PCR and RNA‐seq. ChIP‐PCR analysis was carried out for Notch1 using an antibody specific for acetylated histone 3. Results: Alcohol‐fed mice exhibited colonic (but not small intestinal) hyperpermeability, steatohepatitis, and decreased butyrate/total SCFA ratio in stool. Stem cell, cell lineage, and apical junction marker staining in tissue or organoids from jejunum tissue were not impacted by alcohol. Only chromogranin A (Chga) was increased in jejunum organoids by qPCR. However, colonic tissue and organoid staining exhibited an alcohol‐induced significant decrease in cytokeratin 20+  (Krt20+) absorptive lineage enterocytes, a decrease in occludin and E‐cadherin apical junction proteins, an increase in Chga, and an increase in the Lgr5 stem cell marker. qPCR revealed an alcohol‐induced decrease in colonic organoid and tissue Notch1, Hes1, and Krt20 and increased Chga, supporting an alteration in stem cell fate due to decreased Notch1 expression. Colonic tissue ChIP‐PCR revealed alcohol feeding suppressed Notch1 mRNA expression (via deacetylation of histone H3) and decreased Notch1 tissue staining. Conclusions: Data support a model for alcohol‐induced colonic hyperpermeability via epigenetic effects on Notch1, and thus Hes1, suppression through a mechanism involving histone H3 deacetylation at the Notch1 locus. This decreased enterocyte and increased enteroendocrine cell colonic stem cell fate and decreased apical junctional proteins leading to hyperpermeability. Abstract : Colon stem cell Notch1 stimulates Hes1 and organoid Krt20+ enterocyte cell fate. Notch1 also regulates permeability with increased colonic permeability when Notch1 is suppressed. Alcohol feeding and low microbiome butyrate (dysbiosis) suppresses Notch1 by Histone 3 deacetylation at the Notch1 locus. This results in decreased Krt20+/increased Chga+ cell fate in colonic organoids and increased permeability. Notch1 epigenetic suppression weeks after alcohol may explain chronic alcohol‐induced gut leakiness and its exacerbation by dysbiosis as well as gut leakiness in abstinent alcoholics.